2021
DOI: 10.1007/s42761-021-00087-1
|View full text |Cite
|
Sign up to set email alerts
|

When and How to Regulate: Everyday Emotion-Regulation Strategy Use and Stressor Intensity

Abstract: Contextual factors shape emotion regulation (ER). The intensity of emotional stimuli may be such a contextual factor that influences the selection and moderates the effectiveness of ER strategies in reducing negative affect (NA). Prior research has shown that, on average, when emotional stimuli were more intense, distraction was selected over reappraisal (and vice versa). This pattern was previously shown to be adaptive as the preferred strategies were more efficient in the respective contexts. Here, we invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…In addition, regulation can be an effortful process (Aldao et al, 2015), and keeping regulation efforts to a minimum for less complex hassles can help to conserve resources for future regulation efforts (Hobfoll, 1989). This finding is in line with past research indicating a greater use of regulation on occasions with greater emotional intensity (Blanke et al, 2021; Brans et al, 2013; Dixon-Gordon et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, regulation can be an effortful process (Aldao et al, 2015), and keeping regulation efforts to a minimum for less complex hassles can help to conserve resources for future regulation efforts (Hobfoll, 1989). This finding is in line with past research indicating a greater use of regulation on occasions with greater emotional intensity (Blanke et al, 2021; Brans et al, 2013; Dixon-Gordon et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…We also found that people accepted their emotions less during lockdown, which is consistent with recent research showing that in daily life, people use acceptance less in emotionally intense situations (Blanke et al, 2022). Promisingly, people did not use strategies linked to poor well-being outcomes, like rumination, to a greater extent in lockdown.…”
Section: Discussionsupporting
confidence: 90%
“…For example, in the lab, participants show a consistent preference for regulating with distraction in response to more intense emotional stimuli, but reappraisal in the context of less emotionally intense stimuli (Sheppes et al, 2014). However, support for these findings is mixed in daily life: consistent with the lab, some daily life studies have reported decreases in reappraisal in the context of more intense emotions/stressors (e.g., Blanke et al, 2022), whereas others have reported the opposite (Hiekkaranta et al, 2022). Hiekkaranta et al…”
Section: Antecedents and Consequences Of Emotion Regulationmentioning
confidence: 89%
“…(2022) also found that distraction increased in the context of more intense negative events in daily life, replicating the lab, whereas other studies have reported no association between intensity and distraction (e.g., Blanke et al, 2022). These mixed findings highlight the importance of testing the generalizability of lab research to everyday contexts, where the antecedents of emotion regulation may be more complex.…”
Section: Antecedents and Consequences Of Emotion Regulationmentioning
confidence: 92%